2006
DOI: 10.1185/030079906x132749
|View full text |Cite
|
Sign up to set email alerts
|

A large, naturalistic, community-based study of rivastigmine in mild-to-moderate AD:the EXTEND Study

Abstract: Patients with mild-to-moderate AD switched from previous ChE inhibitor therapy to rivastigmine can obtain measurable benefits, although the treatment effect may be less than in de novo patients. Further research into switching cholinesterase inhibitors is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Only longitudinal follow-up will eventually confirm the hypothesis of brain volume atrophy as an indicator of AD in SMI. However, observation periods of many years are needed to identify reliably who will eventually suffer from dementia [19,20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only longitudinal follow-up will eventually confirm the hypothesis of brain volume atrophy as an indicator of AD in SMI. However, observation periods of many years are needed to identify reliably who will eventually suffer from dementia [19,20] .…”
Section: Discussionmentioning
confidence: 99%
“…Since cognitive impairment develops slowly, it has been suggested that subjective memory impairment (SMI) may precede MCI in the clinical manifestation of AD [19,20] . SMI is defined by the mere subjective feeling of memory decline, but -in contrast to MCI -persons with SMI perform within the normal range on standard neuropsychological tests.…”
Section: Volume Loss Of the Medial Temporal Lobe Structures In Subjecmentioning
confidence: 99%
“…Consequently, subjects enrolled in RCTs may not be representative of AD patients treated in a 'real-world' setting, limiting the external validity of study results [12] . In contrast, studies performed in a naturalistic setting may include a broader range of patients more akin to those seen in clinical practice and are particularly useful for collecting real-life descriptive data on the efficacy and safety of pharmacological treatments for chronic diseases such as AD [13,14] .…”
mentioning
confidence: 99%
“…Results from several open-label studies [8][9][10][11][12][13][14] and from other naturalistic, community-based studies [15][16][17] suggest that the effect of rivastigmine on mood and behaviour might be important. Rivastigmine has been shown to improve and/or delay the symptoms of mood and behaviour, particularly with respect to the symptoms of apathy, anxiety, irritability and agitation [8][9][10]13,[18][19][20] , while reducing and/or delaying the use of concomitant psychotropic medications [9][10][11][12]14,21 .…”
Section: Rationalementioning
confidence: 99%
“…For inclusion into the study, patients were requested to meet the following criteria: clinical diagnosis of mildto-moderate AD [Mini-Mental State Examination (MMSE) [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and for whom rivastigmine treatment is deemed appropriate according to their treating physician; naïve to treatment with rivastigmine; having a regular caregiver/informant (at least three contacts per week); and be able to provide written, informed consent (or having a legal representative who can provide written, informed consent when applicable). Patients were eligible for inclusion if they had been prescribed rivastigmine because of lack or loss of efficacy or intolerance to a previous ChEI.…”
Section: Study Subjectsmentioning
confidence: 99%